A Probabilistic Approach for Assessment of Future Drought in Bagmati River Basin, Nepal - Shrestha, Rajendra Man; Sthapit, Azaya Bikram; Shrestha, Srijan Lal (Nepalese Journal of Statistics, 2018)
Background: The Bagmati River is the rain-fed river in the basin of Nepal. The climate change in rainfall patterns may lead to drought or flashflood in this basin. Drought is a silent and pervasive hazard due to the deficit of water availability. It may have adverse impact on society leading to impact on environment, culture, political and other functions of the region. Objective: This study aims to assess the future drought in the Bagmati River Basin, Nepal. Materials and Methods: Providing Regional Climates for Impact Studies precipitation data was obtained from Department of Hydrology and Meteorology, Kathmandu. The Generalized Extreme Distribution was fitted to respective total precipitations in 3 time-scales using EasyFit software. Standardized Precipitation Index (SPI) method was used to derive SPI for winter drought, SPI for summer drought and SPI for long-term (annual) drought. Results: The results of data analysis showed that winter moderate drought episodes may occur in years 2035, 2042, 2048, 2049, 2051 and 2053. Likewise, summer severe drought episode may occur in 2046. The year 2046 also indicated long-term extreme drought. Moreover, 2030, 2031, 2035, 3040 and 2053 may be long-term moderate drought episodes years in future. Conclusion: There may be winter moderate drought, summer severe drought and a long-term extreme as well as moderate drought during the future period 2030-2060. Nepalese Journal of Statistics, Vol. 2, 75-88